Product–service system mapping for educational service development in public primary schools - Wendy Febrianty Mardhiyah; Primelshaddai Tongguran Manurung; Nanang Alamsyah; Mohammad Rachman Waluyo (Jurnal Mantik, 2026)
This study was conducted to identify the potential implementation of the Product–Service System (PSS) in primary education and to develop a conceptual model suitable for public elementary schools in urban contexts. The research was motivated by the limited application of PSS within the education sector, despite its extensive utilization in manufacturing and service industries to enhance efficiency, innovation, and customer value. A descriptive qualitative approach was employed to obtain comprehensive insights into actual service conditions, management practices, and resource utilization in SDN Kebon Kacang 05 Pagi. Data were collected using structured questionnaires aimed at analyzing institutional characteristics, resource capabilities, and quadrant eligibility within the PSS framework. The findings revealed that the existing condition of the institution was positioned in Quadrant 11 Pure Service, while the desired development direction pointed toward Quadrants 3, 6, and 20. Based on the analysis, five recommended quadrants were proposed: Quadrant 3 (Advice and Consulting), Quadrant 4 (Product-Related Software), Quadrant 5 (Product Lease), Quadrant 6 (Product Renting/Sharing), and Quadrant 7 (Product Pooling). These quadrants represented strategic opportunities to improve educational service quality through knowledge-based consulting, digital integration, resource efficiency, and collaborative resource sharing. The research concluded that PSS has strong potential to enhance innovation, service quality, and sustainability in primary schools